La Pedagogia Nella Prevenzione Del Disagio Dei Presbiteri Di Area Sud Americana Co-Costruttori Di Una Nuova Creazione = Co-builders of a new creation: research for pedagogical motives in an institutional intervention for the prevention of disability in priests/religious - Lozupone, Elvira (2018)
This article seeks the pedagogical motives that arise in the work of W. C. Castilho Pereira Sofrimento Psíquico dos Presbíteros. Dor Institucional. From this essay published in 2012, and never translated in Italian, a free translation of the introduction and the fourth chapter is provided. The work deals with the theme of scandals within the Church as institutional pain and the "sacred silence" that characterizes the burn out of many priests. The proposed strategies of intervention recall constructivism, transdisciplinary approach, Freire's pedagogy and the heart of Salesian pedagogy: they highlight a clear pedagogical epistemology, presenting an intentional, non-formal way of accompaniment. (English)
Keywords: Consecrated Life; Vida Consagrada; Vita consacrata; burn out; Burnout; educación no formal; educazione non formale; fracaso; intervención institucional; Intervention; non-formal education; social constructivism; socio-constructivismo; sociocostruttivismo; Transdisciplinariedad; transdisciplinarietà; Transdisciplinary